Digital Interactive Elements in The Twitter Platform: An Analytical Study - Jabbar, Neeran Waleed; Dabakh, Widad Ghazi (ALBAHITH ALALAMI, 2023)
The primary issue addressed in this research revolves around identifying the interactive elements provided by the Twitter platform and understanding their utilization by digital newspapers with official accounts. These newspapers broadcast content in line with their policies. This study is classified within descriptive research that employed a survey method and content analysis tool. The methodology relies on the "how was it said?" approach to categorize the analysis. The research yielded the following results: Twitter utilized numerous interactive elements for disseminating tweets, which include "text, branching links, hashtags, digital images, digital videos, digital audio, and digital polls." However, these elements were not adopted by the digital newspapers, as they did not utilize digital audio and polls at all.